다항목 자동 혈구 계수 장치 (2025)
[과제] 면역 동태의 정보를 즉시 획득하는 것이 가능하고, 면역 상태를 정확하게 파악할 수 있는 다항목 자동 혈구 계수 장치를 제공한다. [해결 수단] 기초 정보 생성부와, 면역 세포 아군 검출부와, 면역 동태 변화 해석부와, 기억부와, 표시부를 구비하고, 기초 정보 생성부는, 혈액 성분의 혈산 및 백혈구상의 검사 정보와, 림프구의 표면항원과 결합하는 모노클로널 항체의 CD 분류의 해석 정보를 획득하고, 면역 세포 아군 검출부는, 혈액 성분의 혈산 및 백혈구상의 검사 정보와, 림프구의 표면항원과 결합하는 모노클로널 항체의 CD 분류의 해석 정보에 기초하여, 피검자의 면역 상태의 분석에 필요한 면역 세포 아군의 정보를 검출하고, 면역 동태 변화 해석부는, 기초 정보 생성부 및 면역 세포 아군 검출부로 검사된 정보와 기억부에 보존되어 있는 데이터에 기초하여, 피검자의 면역 동태 변화에 관한 정보를 식별하고, 표시부에 영상화하여 제시한다. [Problem] A multi-parameter automatic blood cell counting device that can immediately acquire information of immunodynamics and accurately comprehend immune status is provided.[Solution] The multi-parameter automatic blood cell counting device includes a basic information generator; an immune cell subgroup detector; an immunodynamic change analyzer; a storage; and a display, wherein the basic information generator is configured to acquire examination information of a blood count of blood components and a white blood cell image, and analysis information of a CD classification of monoclonal antibodies that bind to lymphocyte surface antigens, the immune cell subgroup detector is configured to detect information of immune cell subgroups required for analyzing an immune status of a subject based on the examination information of the blood count of the blood components and the white blood cell image, and the analysis information of the CD classification of the monoclonal antibodies that bind to lymphocyte surface antigens, and the immunodynamic change analyzer is configured to identify information related to a change in immunodynamics of the subject based on the information examined in the basic information generator and the immune cell subgroup detector, and data stored in the storage, and to create and display an image of the identified information on the display.